2010
DOI: 10.1140/epje/i2010-10677-0
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics and remodelling of cell packings in epithelia

Abstract: Epithelia are sheets of cells that are dynamically remodelled by cell division and cell death during development. Here we describe the cell shapes and packings as networks of polygons: stable and stationary network configurations obey force balance and are represented as local minima of a potential function. We characterize the physical properties of this vertex model, including the set of ground states, and the energetics of topological rearrangements. We furthermore discuss a quasistatic description of cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
353
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(399 citation statements)
references
References 29 publications
22
353
0
2
Order By: Relevance
“…Similar mechanical models have been employed with great success in a wider context of epithelial and epidermal tissues (13,14,(26)(27)(28)(29). In the case of cells in an ommatidium, modeling revealed that the cells forming the ommatidial ''frame'' (the secondary and tertiary pigment cells, and the bristle group, compare to Fig.…”
Section: Cone Cell Exclusion Volumementioning
confidence: 91%
“…Similar mechanical models have been employed with great success in a wider context of epithelial and epidermal tissues (13,14,(26)(27)(28)(29). In the case of cells in an ommatidium, modeling revealed that the cells forming the ommatidial ''frame'' (the secondary and tertiary pigment cells, and the bristle group, compare to Fig.…”
Section: Cone Cell Exclusion Volumementioning
confidence: 91%
“…The VM originated in studies of the physics of foams in the 1970s and was first applied to model monolayer cell sheets in the early 1980s [47]. Over the past 35 years it has been implemented and extended numerous times and used to study a wide variety of different systems [48][49][50][51][52][53]. The VM is at the core of the cell-based [54] CHASTE [55], a versatile and widely used software package.…”
Section: Introductionmentioning
confidence: 99%
“…1(a)), studies are beginning to clarify how tissue is shaped by forces acting along the plane of the adherens junction, i.e., tension that shortens a cell contact surface and pressure that counteracts the tension to maintain the size of a cell ( Fig. 1(b)) [8,9,10,11,12,13,14,15,16,17]. a e-mail: shuji@complex.c.u-tokyo.jp Measuring tissue stress is therefore useful for deepening our understanding of morphogenesis and its physical constraints.…”
Section: Introductionmentioning
confidence: 99%